The Effect of Immersion Time on the Amount of Fluoride Release in Fluoridated Composite Resin Materials - Ariyani Faizah; Nurul Salsabila; Nilasary Rochmanita Suparno (Interdental Jurnal Kedokteran Gigi (IJKG), 2026)
Introduction: Introduction: The fluoride content in composite resin restorations can help strengthen tooth structure affected by caries. It can also prevent secondary caries through the natural remineralization process. The mechanism of fluoride release occurs when the oral cavity is in an acidic state. It produces hydroxyl ions, which play an important role in stimulating fluoride release. The release of fluoride in composite resins runs constantly over time. The purpose of this study is to determine the effect of immersion time on the amount of fluoride released by fluoride composite resin materials. Materials and Methods: This laboratory experimental study used 25 disc-shaped specimens of fluoride-containing composite resin Tetric N-Ceram Packable (Ivoclar Vivadent AG, Schaan, Liechtenstein) (2 mm thickness × 5 mm diameter). The samples were divided into five groups based on immersion time: 1, 7, 14, 21, and 28 days. Each sample was immersed in artificial saliva at pH 5.5 to simulate acidic oral conditions. The amount of fluoride released was measured using a UV–Vis spectrophotometer at a wavelength of 570 nm. Results and Discussion: Post Hoc LSD analysis showed that the 1-day immersion group differed significantly from all other groups. Significant differences were also found between the 7-day group and the 21-day and 28-day groups, as well as between the 14-day and 21-day groups compared to the 28-day group. However, no significant differences were observed between the 7-day and 14-day groups or between the 14-day and 21-day groups. Fluoride release tended to decrease as immersion time increased. Conclusion: Immersion time significantly affects the amount of fluoride released from fluoride-containing composite resin materials.